Students’ Perception toward PowerPoint Presentation in English Classroom - Lifta Febia Adhani; Cahya Zulianita; Adinda Mutiara Zahra; Fahma Mutiara Malda; Siti Zulfa (JELLT (Journal of English Language and Language Teaching), 2024)
Technology integration in Education has transformed the teaching and learning, offering new possibilities for engagement and pedagogical innovation. Using PowerPoint presentations are gaining prominence as an educational tool in English classroom. However, students face difficulties to follow the material explained by lectures using PowerPoint presentations. It is important to understand students' perceptions toward using PowerPoint presentations in an English classroom. This study investigates students' perceptions and attitudes toward using PowerPoint in English classes within Higher Education. This study used qualitative design. Data was collected through interviews with ten students from several academic years of the English Education Program at one of the universities in Jakarta. The research findings showed that all participants positively perceived the use of PowerPoint presentations. The participants agreed that PowerPoint presentations are beneficial for learning and have some advantages, such as engaging learning, easy comprehension, easy memorization, conciseness of material, and good time efficiency in class. This present study of English education students lays the foundation for future research into the broader influence of PowerPoint presentations on various academic subjects.